Prospective evaluation of p16/Ki‐67 dual‐stained cytology for managing women with abnormal Papanicolaou cytology: PALMS study results. Issue 6 (17th April 2015) - Bergeron, Christine; Ikenberg, Hans; Sideri, Mario; Denton, Karin; Bogers, Johannes; Schmidt, Dietmar; Alameda, Francisco; Keller, Thomas; Rehm, Susanne; Ridder, Ruediger; for the PALMS Study Group
<x xml:space="preserve">Abstract</x> BACKGROUND Testing for the presence of the human papillomavirus (HPV) is widely accepted for triaging Papanicolaou cytology results categorized as atypical squamous cells of undetermined significance (ASC‐US). In contrast, HPV testing has limited use in triaging cytological low‐grade squamous intraepithelial lesions (LSILs) due to prevalence rates of typically >80%. In the current study, the authors assessed the diagnostic performance of p16/Ki‐67 dual‐stained cytology in triaging ASC‐US and LSIL cases within the prospective, multicentric Primary ASC‐US LSIL Marker Study (PALMS). METHODS A total of 575 ASC‐US cases and 529 LSIL cases from a cohort of 27, 349 women who were prospectively enrolled into the PALMS study in 5 European countries were tested with p16/Ki‐67 dual‐stained cytology and Hybrid Capture 2 (HC2) HPV testing. Colposcopy‐guided biopsy results of cervical intraepithelial neoplasia of grade 2 or worse (CIN2+) were used as clinical endpoints. RESULTS p16/Ki‐67 dual‐stained cytology demonstrated comparable (ASC‐US: 94.4% for dual‐stained cytology vs 100% for HC2 testing; P = .317) or lower (LSIL: 85.7% for dual‐stained cytology vs 98.4% for HC2 testing; P = .005) sensitivity for CIN2+, but higher levels of specificity compared with HC2 HPV testing in both ASC‐US (78.7% vs 60.4%; P<.001) and LSIL (53.3% vs 15.6%; P<.001) cases. Positive predictive values for CIN2+ were substantially higher for dual‐stained cytology versus HC2 HPV testing, especially in LSIL, and in ASC‐US cases for women aged <30 years. CONCLUSIONS The clinical usefulness and efficiency of triaging women with ASC‐US or LSIL Papanicolaou cytology results by p16/Ki‐67 dual‐stained cytology testing has been confirmed in this prospective, pan‐European study. The high positive predictive value of dual‐stained cytology for the presence of high‐grade CIN may help to reduce the number of unnecessary colposcopy referrals. Cancer (Cancer Cytopathol) 2015;123:373–81. © 2015 American Cancer Society.